2016
DOI: 10.1007/s00418-016-1508-6
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Fas, FasL, caspase-8 and other factors of the extrinsic apoptotic pathway during the onset of interdigital tissue elimination

Abstract: Elimination of the interdigital web is considered to be the classical model for assessing apoptosis. So far, most of the molecules described in the process have been connected to the intrinsic (mitochondrial) pathway. The extrinsic (receptor mediated) apoptotic pathway has been rather neglected, although it is important in development, immunomodulation and cancer therapy. This work aimed to investigate factors of the extrinsic apoptotic machinery during interdigital regression with a focus on three crucial ini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 50 publications
0
22
0
1
Order By: Relevance
“…Interdigital tissue remodeling (formerly described as, interdigital necrotic zones, INZ) during digit morphogenesis constitutes the most appropriate model to study the biological significance of cell senescence in developing systems (Lorda-Diez et al, 2015). Consistent with the senescence nature of this morphogenetic process cell cycle arrest and overexpression of p21, p63, p73, and the Btg/Tob tumor suppressor gene family are precocious features of interdigit remodeling (Tone and Tanaka, 1997;Vasey et al, 2011;Lorda-Diez et al, 2015;Svandova et al, 2017). Furthermore, SAβ-gal histochemical staining is a very precise marker of INZs ( Figure 2B), and also identifies all other areas of embryonic cell death (Muñoz-Espín et al, 2013;Storer et al, 2013;Lorda-Diez et al, 2019).…”
Section: Cell Senescence Is a Feature Of The Inzsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interdigital tissue remodeling (formerly described as, interdigital necrotic zones, INZ) during digit morphogenesis constitutes the most appropriate model to study the biological significance of cell senescence in developing systems (Lorda-Diez et al, 2015). Consistent with the senescence nature of this morphogenetic process cell cycle arrest and overexpression of p21, p63, p73, and the Btg/Tob tumor suppressor gene family are precocious features of interdigit remodeling (Tone and Tanaka, 1997;Vasey et al, 2011;Lorda-Diez et al, 2015;Svandova et al, 2017). Furthermore, SAβ-gal histochemical staining is a very precise marker of INZs ( Figure 2B), and also identifies all other areas of embryonic cell death (Muñoz-Espín et al, 2013;Storer et al, 2013;Lorda-Diez et al, 2019).…”
Section: Cell Senescence Is a Feature Of The Inzsmentioning
confidence: 99%
“…The implication of the extrinsic pathway in interdigital cell death has been proposed based on the specific expression of members of this cascade in the regressing interdigits. Thus, during the formation of the digits in mice, FAS and FASLG together with active Caspase 8 were preferentially expressed in the regressing interdigit (Svandova et al, 2017). In chick embryos, the immunoreactivity for the ligand TNF alpha was reported in the areas of mesodermal cell death of the developing limb (Wride et al, 1994) and nuclear immunoreactivity for active Caspase 2 was intense in interdigital apoptotic cells (Zuzarte-Luis et al, 2006).…”
Section: Apoptosis Activated By the Extrinsic Pathwaymentioning
confidence: 99%
“…The above results demonstrated that ixazomib enhances caspase 8 activation, which is a well-known initiator caspase in the extrinsic apoptotic pathway. 33 We then analyzed the mechanism by which ixazomib activates the extrinsic apoptosis pathway. It well known that both DR5 and DR4 are important cell surface death receptors, which activate extrinsic apoptotic signaling by recruiting FADD.…”
Section: Dr5 Is Required For Ixazomib-induced Apoptosismentioning
confidence: 99%
“…68 mice was investigated. Samples of gld mice were available from a previous study (Svandova et al 2017). Based on immunohistochemistry, caspase-8 activation was demonstrated also in the gld MC (Fig.…”
Section: Introductionmentioning
confidence: 99%